MacroWikinomics - Tapscott, Don 1947-; Williams, Anthony D. 1974- (Tantor Media, Inc., 2010)
In their 2007 bestseller Wikinomics, Don Tapscott and Anthony D. Williams taught the world how mass collaboration was changing the way businesses communicate, compete, and succeed in the new global marketplace. But much has changed in three years, and the principles of wikinomics are now more powerful than ever. In this new age of networked intelligence, businesses and communities are bypassing crumbling institutions. We are altering the way our financial institutions and governments operate; how we educate our children; and how the healthcare, newspaper, and energy industries serve their customers. In every corner of the globe, businesses, organizations, and individuals alike are using mass collaboration to revolutionize not only the way we work but how we live, learn, create, and care for each other. You'll meet such innovators as: -An Iraq veteran whose start-up car company is "staffed" by over 45,000 competing designers and supplied by microfactories around the country -A "micro-lending" community where 570,000 individuals help fund new ventures-from Azerbaijan to the Ukraine -An online community for people with life-altering diseases that's also a large-scale research project Once again backed by original research, Tapscott and Williams provide vivid, new examples of organizations that are successfully embracing the principles of wikinomics.